Long non-coding RNA PVT1 facilitates cell proliferation by epigenetically regulating FOXF1 in breast cancer. Issue 5 (12th January 2018) - Guo, Guangcheng; Wang, Fang; Han, Mingli; Gu, Yuanting; Duan, Xin; Li, Lin
Abstract : Plasmacytoma variant translocation 1 (PVT1) expression was elevated in breast cancer tissues and correlated to breast cancer progression and prognosis. Abstract : Background : plasmacytoma variant translocation 1 (PVT1) has been identified as an oncogenic long non-coding RNA (lncRNA) in multiple cancers including breast cancer. However, its molecular basis has not been exhaustively elucidated. Methods : RT-qPCR assay was used to detect PVT1 expression in tissues and cells. The effect of PVT1 and FOXF1 on breast cancer cell proliferation was assessed by MTT, colony formation and cell cycle assays. Cell apoptotic rate was measured by flow cytometry via double-staining of Annexin V-FITC and PI. The protein expression patterns of forkhead box f1 (FOXF1) and enhancer of zeste homolog 2 (EZH2) were detected using western blot assays. The subcellular location of PVT1 was analyzed using subcellular fractionation assays. The interaction between PVT1 and EZH2 were demonstrated by RNA-protein pull down and RIP assays. ChIP assay was used to explore whether PVT1 affected FOXF1 expression by recruiting EZH2. In vivo assays were performed to further investigate the roles of PVT1 in breast cancer tumorigenesis. Results : PVT1 expression was elevated in breast cancer tissues and cells. Moreover, higher PVT1 level was positively associated with aggressive pathological status and poor prognosis of breast cancer. PVT1 knockdown suppressed proliferation and induced apoptosis in breast cancer cells. PVT1 silenced FOXF1 expression by recruiting EZH2 to the promoter region of FOXF1, resulting in the increase of H3K27me3 level. EZH2 inhibitor EPZ005687 counteracted PVT1-mediated enrichment effect on H3K27me3 and EZH2 to FOXF1 promoter region. FOXF1 overexpression hampered proliferation and facilitated apoptosis in breast cancer cells. Furthermore, down-regulation of FOXF1 partly abrogated PVT1-knockdown-mediated anti-proliferation and pro-apoptosis effect in breast cancer cells. Finally, PVT1 deficiency suppressed tumor growth by promoting FOXF1 expression in vivo . Conclusion : PVT1 promoted cell proliferation and suppressed apoptosis by epigenetically silencing FOXF1 expression through EZH2 in breast cancer.